PEMBERITAAN METROTVNEWS.COM DAN VIVANEWS.CO.ID TERHADAP SIKAP PARTAI NASDEM TERKAIT PEMERIKSAAN SEKJEN PARTAI NASDEM OLEH KPK - Yuri Alfrin Aladdin (Universitas Bunda Mulia, 2017)
This research is related to the news publicity of the Indonesian media online news Metrotvnews.com and Vivanews.com (Viva.co.id) on the summoning of the National Democrat Party (Partai Nasional Demokrat / Nasdem) Secretary General, Patrice Rio Capella by the Commission of Corruption Eradication (KPK) as a witnes as well as a suspected in the case of the Medan High Court’s judge bribery by North Sumatra Governor, Gatot Pujo Nugroho. Metrotvnews.com owned by tycoon Surya Paloh, who is also Chairman of Nasdem Party. The party join in Great Indonesia Coalition (Koalisi Indonesia Hebat/KIH) supporting President Joko Widodo (Jokowi). Meanwhile, Vivanews.com (Viva.co.id) is an Indonesian media online news owned by tycoon Aburizal Bakrie. He was also Chairman of Golongan Karya Party (Partai Golkar) in the late of 2015 when the scandal happened.The party join in Red-White Coalition, opposed to the Jokowi’s administration. The question’s research about how each of the two portal medias frame their news related the Rio’s case. The research using model framing of Pan and Kosicki, shows that news framing used by Metrotvnews.com proved that the party did not protect Capella at all, while the news framing conducted by Vivanews.com (Viva.co.id) showed that the Nasdem Party as one party in the coalition supporting Jokowi’s administration had many cadres involved in corruption cases.Key words : Semiotic tradition, Metrotvnews.com, Vivanews.com,Patrice Rio Capella, KPK